2014
DOI: 10.1620/tjem.233.49
|View full text |Cite
|
Sign up to set email alerts
|

Expression Levels of Eosinophil Granule Protein mRNAs in Induced Sputum Reflect Airway Hyperresponsiveness and Airflow Limitation

Abstract: Eosinophils are regarded as the major effector cells that produce symptoms in allergic diseases. Activation of eosinophils induces extracellular release of a number of eosinophil granule proteins, including major basic protein (MBP), eosinophil cationic protein (ECP), eosinophil peroxidase (EPO), and eosinophilderived neurotoxin. The objective of this study was to evaluate the differences and significance of the sputum eosinophil% and expression levels of eosinophilic granule protein mRNAs in allergic airway d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
1
5
0
1
Order By: Relevance
“…Other factors, including lysis time and temperature, affect the concentrations of the in ammatory biomarker in the induced sputum supernatant. Studies have shown that the measurement of mRNA expression may be a more sensitive method of evaluating in ammatory mediators in induced sputum [7,39,40]. In accordance with this, our analysis also showed that sputum cell CC16 mRNA but not protein expression in the sputum supernatant was closely and independently correlated with lung function decline (FEV1%pred and FEV1%FVC) in patients with COPD.…”
Section: Discussionsupporting
confidence: 87%
“…Other factors, including lysis time and temperature, affect the concentrations of the in ammatory biomarker in the induced sputum supernatant. Studies have shown that the measurement of mRNA expression may be a more sensitive method of evaluating in ammatory mediators in induced sputum [7,39,40]. In accordance with this, our analysis also showed that sputum cell CC16 mRNA but not protein expression in the sputum supernatant was closely and independently correlated with lung function decline (FEV1%pred and FEV1%FVC) in patients with COPD.…”
Section: Discussionsupporting
confidence: 87%
“…Induced sputum was processed as previously described 19 . The cell pellet was mixed with TRIzol (Gibco) to extract the RNA before RT‐PCR was performed using a RT‐PCR kit (Promega).…”
Section: Methodsmentioning
confidence: 99%
“…Induced sputum was processed as previously described. 19 The cell pellet was mixed with TRIzol (Gibco) to extract the RNA before RT‐PCR was performed using a RT‐PCR kit (Promega). The mRNA of TG2, CD206, macrophage galactose‐type C‐type lectin 1 (MGL), and Arg1 was amplified on an ABI 7500 real‐time PCR system, using SYBR Green master mix (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…We followed a standardized method to obtain induced sputum samples [14]. Sputum samples that contained squamous epithelial cells less than 20% of the total cell count were considered appropriate [15]. We collected at least 0.2 g of stool samples in a stool container (SPL Life Sciences, Pocheon-si, Korea).…”
Section: Samples and Clinical Parametersmentioning
confidence: 99%